2018
DOI: 10.1002/nbm.4004
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpolarized 13C spectroscopic imaging using single‐shot 3D sequences with unpaired adiabatic refocusing pulses

Abstract: Hyperpolarized MRI with 13C‐labeled metabolites has enabled metabolic imaging of tumors in vivo. The heterogeneous nature of tumors and the limited lifetime of the hyperpolarization require high resolution, both temporally and spatially. We describe two sequences that make more efficient use of the 13C polarization than previously described single‐shot 3D sequences. With these sequences, the target metabolite resonances were excited using spectral‐spatial pulses and the data acquired using spiral readouts from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 40 publications
2
23
0
Order By: Relevance
“…for translation to modern clinical MRI scanners. It should be noted, however, that the implementation of 13 C HASTE imaging would provide enhanced in‐plane spatial resolution comparable with that of UTE . In a different murine study, FDG‐PET differentiated between allografts and isografts, showing a significant difference in injected dose per cc of lung (%ID/cc) by day 7; this study further showed that the largest glucose utilization was by CD8+ T cells in particular, a finding echoed in our study.…”
Section: Discussionsupporting
confidence: 77%
“…for translation to modern clinical MRI scanners. It should be noted, however, that the implementation of 13 C HASTE imaging would provide enhanced in‐plane spatial resolution comparable with that of UTE . In a different murine study, FDG‐PET differentiated between allografts and isografts, showing a significant difference in injected dose per cc of lung (%ID/cc) by day 7; this study further showed that the largest glucose utilization was by CD8+ T cells in particular, a finding echoed in our study.…”
Section: Discussionsupporting
confidence: 77%
“…Following injection of hyperpolarized [1- 13 C]pyruvate into an EL4 tumor-bearing mouse, 16 axial images of [1- 13 C]lactate and [1- 13 C]pyruvate were acquired using a single-shot, 3D volume imaging sequence. 15 The subcutaneous tumors showed pyruvate uptake and conversion to lactate, with consistently a region of high 13 C lactate signal intensity at the tumor base (Figures 3 and 4) (Supporting Information Figure S1). [1- 13 C]lactate and [ 12 C]lactate were detected in excised tumor sections by DESI MSI and metabolic maps generated from their peak intensities (Figure 3 and Supporting Information Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…MRI data were processed using an in-house MatLab (version R2019b, MathWorks, Natick, MA) script. 15 The MSI .raw data files were converted into .mzML files using ProteoWizard msConvert version 3 (open source) 18 and compiled into an .imzML file. 19 Subsequent data processing was performed in SCiLS Lab (version 2019c, Bruker Daltonik, Bremen, Germany).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spin-echo or steady-state methods are promising for providing substantial improvements in SNR and resolution. 80,81 Autonomous scanning methods with integrated frequency, power and timing corrections 82 have the potential to provide more robust and reproducible results. There are promising new kinetic models that can remove confounding factors such as perfusion, and more robust analysis methods.…”
Section: Discussionmentioning
confidence: 99%